Good Corporate Governance sebagai Instrumen Hukum dalam Penguatan Regulasi Badan Usaha Milik Desa - Nur Setyowati (Recht Studiosum Law Review, 2025)
The application of Good Corporate Governance (GCG) principles in Village-Owned Enterprises (BUMDes) aims to enhance efficiency, transparency, accountability, and sustainability in managing village-based economies. This research employs a doctrinal legal method with statutory and conceptual approaches. The data used comprise secondary sources from legislation, legal journals, and relevant literature. The analysis reveals that GCG principles are implicitly accommodated in various regulations governing BUMDes, with explicit provisions only found in Article 24 paragraph (6) letter a of the Minister of Villages Regulation Number 3 of 2021. The study highlights the necessity of strengthening GCG principles through more detailed and effective legal frameworks in higher-level regulations. This reinforcement is expected to promote professional, integrated, and sustainable governance of BUMDes, contributing to competitive village economic development. Keywords: Village-Owned Enterprises; Good Corporate Governance; Regulations.